2019
DOI: 10.1103/physrevb.99.035106
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Dirac cones and Van Hove singularity in an organic Dirac fermion system

Abstract: We propose an experimental method to examine the in-plane anisotropy of electronic structure in layered conductors. In the method, we measure the interlayer magnetoresistance as a function of in-plane magnetic field orientation. We applied it to an organic Dirac fermion system α-(BEDT-TTF) 2 I 3 to experimentally determine the orientation of the anisotropic Dirac cones. It is concluded that the long axis of the elliptic constant-energy contours of the Dirac cone is tilted by approximately −30° from the crystal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 29 publications
7
14
0
Order By: Relevance
“…Moreover, the remarkably small doping considered above quantitatively agrees with what has been suggested by transport experiments in out-of-plane magnetic fields [53,63,65,78] and a relevant calculation within a linearresponse theory [64]. It also does not conflict with more recent magnetotransport studies in an in-plane magnetic field [51,79].…”
Section: Comparison With Experiments In α-(Bedt-ttf) 2 Isupporting
confidence: 88%
“…Moreover, the remarkably small doping considered above quantitatively agrees with what has been suggested by transport experiments in out-of-plane magnetic fields [53,63,65,78] and a relevant calculation within a linearresponse theory [64]. It also does not conflict with more recent magnetotransport studies in an in-plane magnetic field [51,79].…”
Section: Comparison With Experiments In α-(Bedt-ttf) 2 Isupporting
confidence: 88%
“…Pressure-dependent optical studies [132,163] reveal the presence of additional charge excitations, also inferred from magnetotransport [237]. The effect of interlayer magnetoresistance in the case of tilted Dirac cones was subsequently discussed [214,238,239] and suggested that angular-dependent measurements could reveal the in-plane anisotropy of electronic structure.…”
Section: Dirac Electronsmentioning
confidence: 98%
“…Although the FS anisotropy for EuMnBi 2 is comparable to that for SrMnBi 2 [13], the FS size for EuMnBi 2 is approximately one-sixth of that for SrMnBi 2 , as estimated from the quantum oscillation frequency; B F ∼ 20 (130) T for EuMnBi 2 (SrMnBi 2 ) [5,8]. The temperature broadening of the FS may effectively damp the anisotropy of interlayer MR and hence the r value, when the magnitude of broadening (∆k) is comparable to the radius of the FS [14]. For EuMnBi 2 , ∆k/k F ∼ k B T/ℏv F k F is estimated to be ∼ 3×10 −4 at 1.4 K, where k F ∼ 0.03 Å −1 (ℏv F ∼ 9 eVÅ) is the Fermi wave-vector (velocity) along the Γ-M direction [11].…”
Section: (C)-(f)]mentioning
confidence: 96%